Naval War College (U.S.) records - Naval War College (U.S.)
Chiefly letters to Stephen Bleecker Luce and H.C. Taylor during their terms as president of the U.S. Naval War College. Subjects include appropriations, curriculum, lecturers, and a proposal for a school with post-graduate courses for naval officers. Correspondents include Charles C. Cornwell, A.T. Mahan, Thomas Perry, David D. Porter, Francis M. Ramsay, and William Ledyard Rodgers.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Cornwell, Charles C., -- -1904 -- Correspondence; Luce, Stephen Bleecker, -- 1827-1917 -- Correspondence; Mahan, A. T. -- 1840-1914 -- Correspondence; Perry, Thomas -- Correspondence; Porter, David D. -- 1813-1891 -- Correspondence; Ramsay, Francis M. -- 1835-1914 -- Correspondence; Rodgers, William Ledyard, -- 1860-1944 -- Correspondence; Taylor, H. C. -- 1845-1904 -- Correspondence; United States. -- Navy; Naval education -- United States; College presidents